The Influence of Digital Technology Utilization and Adoption on the Operational Efficiency of MSMEs in the Era of Digital Transformation - Julianda Jahid Muttaqin; Afidah Nur Aslamah; Osly Usman; Ryna Parlyna (Journal of Strategic Marketing and Innovation, 2025)
The accelerated improvement of digital technology has contributed substantial adjustments to the way Small enterprise within the capital city in Jakarta conduct their business operation. The growth of internet access, the extensive use of smartphones, and the increasing availability of digital platforms have opened wider possibilities for improving business efficiency. This study aims to explore how the use and acceptance of digital technology influence the operational effectiveness of local business owners in Jakarta within the framework of digital transformation. A quantitative explanatory method is used in this research, gathering information via an online survey sent to MSME owners in Jakarta. The variables investigated in this study include Digital Technology Utilization (X1), Digital Technology Adoption (X2), and Operational Efficiency (Y). The findings from this research are anticipated to illustrate how the effective use and adoption of digital tools and platforms can support productivity improvement, cost efficiency, and more structured business processes. Furthermore, this research provides insights into the level of digital readiness among MSMEs and offers practical implications for enhancing digital adoption within the Indonesian MSME sector.